2009
DOI: 10.2166/aqua.2009.006
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ferric salts in removing low levels of dosed copper from NOM-containing natural water

Abstract: Water utilities dose copper in drinking water systems to inhibit/kill microorganisms including algae. Under conditions observed in the systems, the majority of dosed copper is reported to be in dissolved forms of Cu-NOM and inorganic compounds. High concentrations (40 mg/L) of ferric salts are reported to be able to remove large amounts of copper. However, the fate of dissolved copper when a small amount of ferric salts (,2 mg/L) is present in natural water or in the distribution pipes when they are released f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Chlorine and chloramine are also strong oxidizing agents which can compete with Cu 2+ to react with iron. Our earlier study [26] and studies by others [8,10] found little dissolved copper existing in natural water in the form of cupric ions, as most of the copper existed as Cu-NOM complexes. This finding further excludes the possible reaction between free cupric ions and iron.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Chlorine and chloramine are also strong oxidizing agents which can compete with Cu 2+ to react with iron. Our earlier study [26] and studies by others [8,10] found little dissolved copper existing in natural water in the form of cupric ions, as most of the copper existed as Cu-NOM complexes. This finding further excludes the possible reaction between free cupric ions and iron.…”
Section: Introductionmentioning
confidence: 71%
“…as a nitrification inhibitor), little research has been conducted on dissolved Cu(II) removal by low concentration (< 2 mg/L) iron pipe corrosion products released from corroded or damaged pipes in distribution systems like the G&AWSS. Preliminary experiments using water from Mundaring Weir showed adsorption of dissolved Cu(II) by Fe(OH) 3 flocs present at trace concentrations, with the adsorption obeying Langmuir or Freundlich adsorption isotherms [26].…”
Section: Introductionmentioning
confidence: 99%